Aplikasi Multiplatform Sayur Kita untuk Meningkatkan Efisiensi Pedagang Pasar - Bima Aprie Yudha; Saeful Anas Fitri Antopo; Neng Linda Badratul Laela (Jurnal Teknologi Informasi dan Multimedia, 2024)
Markets are an essential part of the economic ecosystem, often facing various challenges for traders. One of the issues they encounter is the limited time for conducting transactions with both consumers and suppliers. This condition significantly impacts business performance and the quality of stock, influenced by various factors such as weather, time constraints, and the shipping process. This research aims to determine and analyze the development of applications that make buying and selling easier between traders and suppliers online, which can be accessed at any time. This application is integrated into various platforms, both via mobile and web, to enable traders to carry out transactions quickly, effectively and efficiently in terms of time, ef-fort and cost. Apart from that, this research is to facilitate transactions between market traders and suppliers, as well as expand the reach of online markets, especially regarding time con-straints and stock availability. By adopting an integrated multiplatform application develop-ment approach, this research aims to facilitate transactions between market traders and suppli-ers, as well as expand the market reach online, particularly addressing time limitations and stock availability. The development method used is the Waterfall method, which includes re-quirements analysis, system design, implementation, testing, and maintenance. The result of this research is an application called "Sayur Kita," a cross-platform application that helps traders con-duct transactions quickly and efficiently through mobile and web platforms, usable on various devices. Testing was conducted using the black box method, and the results showed that all fea-tures operated as expected. Therefore, this application can help improve the efficiency of market traders in conducting transactions with suppliers and traders online.